Taxonomic evaluation of the Grallaria rufula (Rufous Antpitta) complex (Aves: Passeriformes: Grallariidae) distinguishes sixteen species - Isler, Morton L.; Chesser, R. Terry; Robbins, Mark B.; Cuervo, Andrés M.; Cadena, Carlos Daniel; Hosner, Peter A. (Zootaxa, 2020)
Populations in the Rufous Antpitta (Grallaria rufula) complex occupy humid montane forests of the Andes from northern Colombia and adjacent Venezuela to central Bolivia. Their tawny to cinnamon-colored plumages are generally uniform, featuring subtle variation in hue and saturation across this range. In contrast to their conservative plumage, substantial vocal differences occur among geographically isolated or parapatric populations. Working within the framework of a comprehensive molecular phylogeny, we reexamined species limits in the G. rufula complex, basing taxonomic recommendations on diagnostic differences in vocalizations and considering identifiable differences in plumage where pertinent. We identified 16 populations for species designation, including seven populations previously described as subspecies and, remarkably, six new species described herein. Within one of these species, we identified less robust vocal differences between populations that we designate as subspecies. Geographic variation exists within another species, but its critical evaluation requires additional material. Taxonomic revisions of groups consisting of cryptic species, like the Grallaria rufula complex, are imperative for their conservation. Rather than widespread species as currently defined, these complexes can comprise many range-restricted taxa at higher risk of extinction given the continuing human pressures on their habitats.